Synthetic control over the binding configuration of luminescent sp3-defects in single-walled carbon nanotubes - Settele, Simon; Berger, Felix J.; Lindenthal, Sebastian; Zhao, Shen; El Yumin, Abdurrahman Ali; Zorn, Nicolas; Asyuda, Andika; Zharnikov, Michael; Högele, Alexander; Zaumseil, Jana (Nature Communications, 2021)
The controlled functionalization of single-walled carbon nanotubes with luminescent sp3-defects has created the potential to employ them as quantum-light sources in the near-infrared. For that, it is crucial to control their spectral diversity. The emission wavelength is determined by the binding configuration of the defects rather than the molecular structure of the attached groups. However, current functionalization methods produce a variety of binding configurations and thus emission wavelengths. We introduce a simple reaction protocol for the creation of only one type of luminescent defect in polymer-sorted (6,5) nanotubes, which is more red-shifted and exhibits longer photoluminescence lifetimes than the commonly obtained binding configurations. We demonstrate single-photon emission at room temperature and expand this functionalization to other polymer-wrapped nanotubes with emission further in the near-infrared. As the selectivity of the reaction with various aniline derivatives depends on the presence of an organic base we propose nucleophilic addition as the reaction mechanism.